2022
DOI: 10.1080/19490976.2022.2134689
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacterial extracellular vesicles: important players in regulating intestinal microenvironment

Abstract: Intestinal microenvironment dysbiosis is one of the major causes of diseases, such as obesity, diabetes, inflammatory bowel disease, and colon cancer. Microbiota-based strategies have excellent clinical potential in the treatment of repetitive and refractory diseases; however, the underlying regulatory mechanisms remain elusive. Identification of the internal regulatory mechanism of the gut microbiome and the interaction mechanisms involving bacteria-host is essential to achieve precise control of the gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 167 publications
0
29
0
Order By: Relevance
“…In recent years, both our understanding of the gut microbiota and its complex relationship to disease have significantly increased. For instance, obesity contributes to altered intestinal microenvironments that support a greater variety of virus species than those found in hosts that are slimmer 32 . In this context, pathogenic mutations that can cause severe disease are more likely to be produced.…”
Section: Pathogenesis and Pathophysiology Of Obesitymentioning
confidence: 99%
“…In recent years, both our understanding of the gut microbiota and its complex relationship to disease have significantly increased. For instance, obesity contributes to altered intestinal microenvironments that support a greater variety of virus species than those found in hosts that are slimmer 32 . In this context, pathogenic mutations that can cause severe disease are more likely to be produced.…”
Section: Pathogenesis and Pathophysiology Of Obesitymentioning
confidence: 99%
“…Furthermore, to clarify the gut microbiota‐targeted mechanisms of miR‐29a, we explored the relationship between these gut bacteria and HFD‐induced inflammation and examined the expression of IL‐6 in the gut and liver. Previous studies have reported that the abundance of Parabacteroides , Bacteroides , and Mucispirillum is positively correlated with the blood levels of IL‐6 and LPS in chronic inflammation [ 70,71 ] and the brain cortex. [ 72 ] Together with our earlier report, [ 73 ] the present work confirmed that miR‐29a could modulate IL‐6 expression and reduce tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve a precise modulation of gut microbiome with clinical effectiveness, it is essential to identify the regulatory mechanisms that control the host-microbiome interactions. Recently, microbiome-released extracellular vesicles (MEVs) have emerged as a key delivery mechanism in controlling intestinal microenvironment and bacteria-host communications 13,48 . MEVs are small membrane-bound phospholipid vesicles that encase a spectrum of biologically active molecules (i.e., proteins, mRNA, miRNA, DNA, carbohydrates, and lipids) that protect them from lytic enzymes and RNases in the extracellular environment 49 and facilitate their horizontal transfer across both short and distant locations, such as the brain 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…have emerged as a key delivery mechanism in controlling intestinal microenvironment and bacteria-host communications 13,48 . MEVs are small membrane-bound phospholipid vesicles that encase a spectrum of biologically active molecules (i.e., proteins, mRNA, miRNA, DNA, carbohydrates, and lipids) that protect them from lytic enzymes and RNases in the extracellular environment 49 and facilitate their horizontal transfer across both short and distant locations, such as the brain 50,51 .…”
Section: Discussionmentioning
confidence: 99%